Elevations in Liver Transaminases in COVID-19: (How) Are They Related? - Pott-Junior, Henrique; Bittencourt, Natália Queiroz Prado; Chacha, Silvana F. G.; Luporini, Rafael Luís; Cominetti, Marcia Regina; Anibal, Fernanda de Freitas (Frontiers in Medicine, 2021)
Liver involvement in COVID-19 is not yet well understood, but elevations in liver transaminases have been described to occur in 14% to 53% of the cases and are more frequently seen in severe disease. This cross-sectional study explored the relationship between the elevations in liver transaminases and inflammatory parameters in 209 adults with COVID-19. Demographic and clinical data, serum levels of inflammatory cytokines and liver aminotransferases were analyzed. Three groups were formed according to the liver transaminase abnormalities: (I) Normal transaminases, (II) Borderline transaminases elevation, and (III) Mild to severe transaminases elevation. Altered liver transaminases were directly related to disease severity, showing association with the NEWS2 score at admission and greater need for ICU or death. Moreover, higher levels of IL-2 and CRP were associated with borderline transaminases elevations, whereas higher levels of IL-10 and Neutrophil to Lymphocyte ratio were associated with mild to severe transaminases elevation. These results reinforce the importance of liver transaminases in patients with COVID-19 as a complementary marker for disease severity and also point to them as a parameter reflecting the continuous dynamics between viral infection and the immune response.